Use of ICT and Students' Personal and Social Development at Higher Education Level - Abid Hussain Chaudhry; Misbah Malik (CSRC Publishing, Center for Sustainability Research and Consultancy Pakistan, 2019)
The substantive purpose of this study was to identify the effect of using ICT on students' personality development. Population of the study consisted of students of two universitiesof Lahore. Sample of the study comprised randomly selected 242 students. A self-developed and validated instrument was used for data collection. Instrument comprised two sections one contained demographic variables and other statements related to personality development of students.  A pilot study was conducted to validate the instrument. The reliability index (cronbach alpha) was .83 which is statistically significant. Data were analyzed through SPSS. t- test was run to identify mean difference in personality development of male and female students. ANOVA was applied to see mean difference in the responses of students, regarding their personality development in different programs. Results showed that use of ICT has a profound effect on Female students' personality. Results of ANOVA revealed that students of BBA department show more effect of ICT on their personality. Recommendations were made on the basis of findings.